Microelectronics sensors and devices - Mukhzeer Mohamad Shanimin e editor; Noraini Othman e editor (Penerbit Universiti Malaysia Perlis, 2014)
The book is a concise, concentrated presentation, limiting coverage to only those concepts necessary for the understanding of devices and circuits